The Effect of Accent(s) and Pronunciations(s) of English on Bangladeshi English Language Learners’ Listening Skill Acquisition Process - Zarin, Ismat (EAST WEST JOURNAL OF HUMANITIES, 2013)
Listening, the most vital skill in language acquisition, is often regarded also as the most difﬁcult skill to attain by second language learners. This study investigates Bangladeshi English language learners’ problems in acquiring listening skills in connection to pronunciation(s) & accent(s) of English and its possible connection to the motivation of learners. To conduct the study, a number of 255 ﬁrst year undergraduate students from twenty universities in Bangladesh were selected as subjects. The ﬁndings of the study suggest that native accent(s) and pronunciation(s) of English play a critical role in listening skills acquisition process and that motivation to learn listening skills among English language learners in Bangladesh is affected by native pronunciation(s) and accent(s) of English.